A study on the clinical and sonological correlation in the diagnosis and management of acute appendicitis in a tertiary care centre - Mudavath, Keerthi; K., Thinagaran (International Surgery Journal, 2019)
Background: Acute appendicitis is the most common acute surgical condition of the abdomen requiring early intervention. The diagnosis is often challenging and the decision to operate in an emergency setting is always debatable. Alvarado score for diagnosis of acute appendicitis is easy and additional tools like sonography results in accurate diagnosis. The aim was to evaluate accuracy of the clinical Alvarado scoring system, radiological findings and histopathological examination for the diagnosis of acute appendicitis. Methods: 100 cases of acute abdomen admitted in PES institute of medical sciences and research, Kuppam from December 2016 to June 2018 were included. Clinical examination was done and all patients were subjected to ultrasound abdomen examination and other relevant blood and imaging investigations. Results: Out of 100 patients 62 were males and 38 were Females. Most common symptom was pain in the right iliac fossa and patients with Alvarado Score 7 or > 7 subjected to USG followed by emergency appendectomy showed positive operative findings and histopathological findings. The overall specificity of abdominal USG in the diagnosis of acute appendicitis was 88.09% and sensitivity was 95.37%. Conclusions:The Alvarado scoring system combined with ultrasound can therefore be used as a cheap and less expensive useful, reliable and non invasive way of confirming acute appendicitis thus helps in reducing negative appendectomy rate. The overall accuracy of diagnosis of acute appendicitis goes up to 90% with positive histopathological findings.